Digitization of Public Services: A Systematic Literature Review - Leão, Heloise Acco Tives; Canedo, Edna Dias (Anais do Simpósio Brasileiro de Qualidade de Software (SBQS); 2018: Anais do XVII Simpósio Brasileiro de Qualidade de Software, 2018)
This paper presents a systematic literature review of the digitization of services carried out by the governments of several countries. The main contribution of this work is the identification of the processes and methodologies adopted by these governments to provide their services to the citizen. These results serve as inputs to guide an analysis of the initial efforts of the Brazilian Government in the construction of a digital platform for the provision of its services directed to the citizen, seeking to analyze their needs and improving the services currently provided.